TRAINING PRE-SERVICE TEACHERS ON PLURILINGUISM: CHALLENGES, PERCEPTIONS AND DICATIC SUGGESTIONS - Souhila BENZERROUG (Universitaria Publishing House, Craiova, 2021)
The present research paper highlights the importance of plurilingual competence and plurilingual approach to language education in pre-service teacher training taking students at the Teacher Training College of Bouzareah-Algeria as a case study. The study is designed to gain insight into the development of plurilingual competence and the implementation of plurilingual approach to foreign language teaching and learning in the pre-service program that is addressed to the students of the departments of French and English in their final year of university studies as they guarantee a professionalization of the pre-service training (Kervran, 2005; Castelloti, 2002). To achieve the above mentioned aims, the researcher employed a qualitative method by using semi-structured interviews with pre-service teachers being trained to teach foreign languages in the secondary education as well as Master students of Didactics who are teaching in the field area aiming at suggesting a didactic model for integrating plurilingual approach for teacher education.